Kedudukan dan Tanggung Jawab Manusia dalam Alam Menurut Thomas Berry - Alfonsius Jeujanan (Kelompok Studi Mitra Skolastikat MSC PinelengINELENG, 2023)
Thomas Berry is a priest and geologist who seeks to find the relationship between humans and the earth to answer ecological challenges. Since childhood he has been interested in ecological issues. Through his writings he tries to invite us to build a mutually developing relationship with the earth's community. Thomas Berry's thoughts were influenced by two figures and eastern religions, especially Confucianism. The harmony between cosmic and human in Confucian thought is in line with Thomas Berry's thought about the Ecozoic era. The era in which all living systems are in a relationship that mutually develops and forms an integral community of life. Humans are members of the earth community and have a responsibility to promote progress and prosperity in the earth community. Humans are guardians of nature and not destroyers of nature. The focus of this study is to discuss on the position and responsibility of humans in nature according to Thomas Berry. With the help of descriptive and analytical methods, this paper seeks to explain Thomas Berry's thoughts while simultaneously providing inspiration for nature protection